FEATURES OF THE TECHNOLOGY OF GROWING BROCCOLI CABBAGE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
In this article, information on the peculiarities of obtaining a high and high-quality yield of broccoli cabbage by controlling its growth and development, taking into account its attitude to the complex of environmental conditions.